COALITION PRESIDENTIALISM IN THE STATE OF SAO PAULO - Gaspardo, Murilo [UNESP]; Marchioni, Artur [UNESP] (Escola Magistratura Rio Grande Norte, 2016)
The basic theoretical framework of this dissertation is the concept of coalition presidentialism and the various empirical researches that were applied in the analysis of relations between the federal Executive and Legislative spheres after the promulgation of the 1988 Constitution, especially the works of Fernando Limongi and Argelina Figueiredo. We tried to understand how the governability is built in the Brazilian legal-political system (coalition presidentialism) through the agenda power of the President, the concentration of the Board's decisions on political party leaders (due to the decision-making structure expected in its internal regulation), and the sponsorship. As a counterpoint, we appealed to the criticism of this way of getting governability, developed by Marcos Nobre with his concept of peemedebismo, practice characterized by the formation of supermajorities parliamentarians and by a system of locks to any attempts at structural political changes. Based on these theoretical and empirical references, we tried to investigate the hypothesis of the relationship between the Executive and Legislative powers in the State of Sao Paulo occur according to the same logic of coalition presidentialism.
Keywords: Public Law; Democracy; Executive-Legislative Relationship